2016
DOI: 10.1590/2358-2936e2016022
|View full text |Cite
|
Sign up to set email alerts
|

Infestation by the epibiont Octolasmis lowei in a portunid crab assemblage from a subtropical coast

Abstract: We investigated the infestation by Octolasmis lowei Darwin, 1851 in branchial chambers of the portunid Achelous spinimanus (Latreille, 1819), Arenaeus cribrarius (Lamarck, 1818), Callinectes danae Smith, 1869, and Callinectes ornatus Ordway, 1863. We evaluated how infestation is related to host maturity, molt stage, carapace width and sex. Th e infestation probability increases with host carapace width, and infested crabs were more likely to be adults Nauplius BraZIlIan crustacean socIety Nauplius BraZIlIan cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…In this study, sample found the average weight of females is greater than that of males, this is in contrast to that obtained by Pudiawati and Patria (2017) on S. oceanica in mangrove area in Tanjung Lesung, Banten, Indonesia. However, Santos and Bueno (2002); Silva-Inácio et al (2016) stated that there was no correlation found between the prevalence of O. lowei infestation and the carapace width of males or females in blue crabs and portunid crab.…”
Section: Mercury (Hg) Accumulation In Parasites and Crab Hostsmentioning
confidence: 99%
“…In this study, sample found the average weight of females is greater than that of males, this is in contrast to that obtained by Pudiawati and Patria (2017) on S. oceanica in mangrove area in Tanjung Lesung, Banten, Indonesia. However, Santos and Bueno (2002); Silva-Inácio et al (2016) stated that there was no correlation found between the prevalence of O. lowei infestation and the carapace width of males or females in blue crabs and portunid crab.…”
Section: Mercury (Hg) Accumulation In Parasites and Crab Hostsmentioning
confidence: 99%